Pengaruh Motivasi Kerja, Kerja Sama Tim Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Personel Kepolisian Biddokkes Polda Sultra - Sumardin Sumardin; Ibnu Hajar; Aidin Hudani Awasinombu; Patwayati Patwayati; Nursaban Rommy Suleman; Nofal Nur (Pascasarjana Universitas Halu Oleo, 2023)
The purpose of this study was to examine and explain the effect of work motivation, teamwork and non-physical work environment on the performance of the North Sulawesi Regional Police Biddokkes personnel either simultaneously or partially. The approach of this study is quantitative using a survey method. The data was collected by cross section by using a one-line questionnaire via the link: https://forms.gle/xXS8ShLBhmbJxBBx5. The population of this study were all 49 members of the Biddokkes Police of the Southeast Sulawesi Regional Police and all of them were used as research respondents. The analytical tool used is multiple linear regression analysis.The results showed that work motivation, teamwork and non-physical work environment simultan eously had a significant effect on the performance of the Biddokkes Police personnel of the Southeast Sulawesi Regional Police. Furthermore, the partial test results of work motivation have a positive and significant effect on personnel performance. Then teamwork proved to have a positive and significant effect on personnel performance. A good non-physical work environment contributes significantly or significantly to the improvement of personnel performance. This means that the better the implementation of work motivation, teamwork and non-physical work environment, the performance of personnel will increase significantly. This result is also reinforced by the respondent's statement based on the description of the variables of work motivation, teamwork and non-physical work environment and personnel performance.